Coenzyme Q10 Prevents Mitochondrial Dysfunction and Facilitates Pharmacological Activity of Atorvastatin in 6-OHDA Induced Dopaminergic Toxicity in Rats - Prajapati S.K.; Garabadu D.; Krishnamurthy S. (My University, 2025)
Atorvastatin (ATV) generally used to treat dyslipidemia is also reported to have effect against 6-hydroxydopamine (6-OHDA) induced neurotoxicity. Additionally, atorvastatin can interfere with mitochondrial function by reducing the level of Q10. Therefore, the therapeutic effect of atorvastatin (20 mg/kg) could be compromised. In this context, the present study evaluated the effect of ATV supplemented with Q10. 6-OHDA was unilaterally injected into the right striatum of male rats. On day 8 of 6-OHDA infusion, ATV (20 mg/kg), Q10 (200 mg/kg), and their combination were administered per oral for 14 days. On day 21, there was significant loss of striatal dopamine indicating neurotoxicity. The combination of ATV+Q10 showed significant amelioration of dopamine (DA) toxicity compared to individual treatments. Similarly, ATV+Q10 compared to individual treatment significantly decreased the motor deficits induced by 6-OHDA. Further, 6-OHDA induced mitochondrial dysfunction in the substantia nigra pars compacta (SNpc). There was significant decrease in mitochondrial complex enzyme activities and mitochondrial membrane potential (MMP). Treatment with ATV and ATV+Q10 ameliorated mitochondrial dysfunction by increasing complex enzyme activities; however, only ATV+Q10 were able to stabilize MMP and maintained mitochondrial integrity. Moreover, there was significant induction of oxidative stress as observed from increase in lipid peroxidases (LPO) and nitrite (NO), and decrease in super oxide dismutase (SOD). Treatment with ATV+Q10 significantly altered the above effects indicating antioxidant activity. Furthermore, only combination of ATV and Q10 decreased the 6-OHDA induced expression of cytochrome-C, caspase-9 and caspase-3. Therefore, current results provide evidence that supplementation of Q10 with ATV shows synergistic effect in reducing dopamine toxicity. © 2017, Springer Science+Business Media New York.